Innovative approaches to nuclear energy density optimization for enhanced power generation and waste minimization - Muellner Gufler Kromp; Frechette Pascual Zambetakis; Wood Wood (Institute of Computer Science (IOCS), 2023)
Nuclear energy has emerged as a viable low-carbon option for electricity generation, but traditional reactor designs face challenges regarding energy density and nuclear waste management. This research explores innovative approaches to optimize nuclear energy density while minimizing long-term environmental impact through reduced waste production. The study compares a traditional Pressurized Water Reactor (PWR) with an advanced Molten Salt Reactor (MSR) as the innovative technology. The objectives are to maximize energy density and minimize nuclear waste. A multi-objective optimization model is formulated, incorporating safety, operational, and environmental constraints. Numerical results demonstrate that the MSR achieves a higher energy density (30 MW/kg) than the PWR (20 MW/kg) and produces less waste (0.2 kg/MW vs. 0.5 kg/MW). The research highlights the potential benefits of innovative nuclear technologies and emphasizes the importance of safety evaluations, regulatory considerations, and economic viability for practical implementation. Collaborative efforts and supportive policies are crucial to realizing a sustainable and low-carbon energy future through advanced nuclear solutions